Pelvic Fracture in a Cat - Precontouring of the Plate Based on Allogenic 3D Model and its Application - Kim, Kihoon; Shin, Jaiho; Kim, Jaehwan; Kim, Hwi-Yool (Acta Scientiae Veterinariae, 2022)
Background: Pelvic fractures are commonly ecountered in cats. The ilium is included in approximately 50% of pelvic fractures in cats. Although conservative management of the pelvic fracture is known to have good prognosis, surgical fixation is recommended for the pelvic fractue with ilial fractures. 3D printing is an accurate digital modeling method by converting two-dimensional (2D) image into 3D model. 3D printing in veterinary medicine have been described in the various orthopedic diseases such angular limb deformities or fractures. The use of 3D model for presurgical planning is helpful to improve the results of complex surgical interventions. The objective of this study is to identify the usefulness of fabricating 3D models based on allogenic 2D data with aid of 3D printer program. Case: A 4-year-old spayed female domestic shorthair cat presented with hindlimb lameness. Radiography revealed left ilial body fracture with multiple fractures including left tuber ischium, pubic symphysis, and bilateral cranial ramuses of pubis. Digital imaging and communication in medicine (DICOM) files of the complete ilium were extracted from a CT scan of a healthy and castrated male cat of same breed. Volume rendering images were prepared by Slicer program based on DICOM files. After acquired 3D data were converted to STL (Standard Triangulation Language) file for the 3D printing machine, non-fracture involved area was removed except the left ilium using the Meshmixer® soft-ware and then data was stored as STL files again. The length of 3D model was adjusted to actual size using 3D printer firmware based on actual size of the ilial length. Subsequently, 3D modelling was performed using 3D printer. The plate was precontoured to conform to the lateral surface of the 3D model. Internal fixation using precontoured plate resulted in accurate bone alignment. The alignment of the ilium remained appropriate throughtout the follow-up period. Complete union was identified 6 months after surgery. Discussion: Although the most common method for the ilial fractures is the application of bone plates to the lateral side of the ilium, bone plate fixation is more challenging in cats owing to the small bone size and small surface area of the fracture sites compared to dogs. Therefore, it is important to make accurate presurgical planning for successful result of a surgery. 3D printing based on actual patient have several limitations including time for complete printing process and additional anesthetic episode to acquire computed tomography (CT) images. However, in simple cases, a presurgical CT scan may not be necessary if the plate can be precisely precontured based on the data from the other patient. In this way, the additional financial burden for CT examination also might be reduced. On the other hand, technical difficulty of utilizing hardware and software, and financial availability were another drawback. However, in this current study, most of limitations regarding conventional 3D printing based on actual patient were overcome by the application of the fused deposition modeling (FDM) technology with allogenic data. In the current study, total time for fabrication of 3D model based on FDM technology, was less than 3 h, which are much shorter than the time for conventional 3D printing. The difference of the ilial length between the actual patient and the 3D model was adjusted through the firmware program. Thus, differences of the conformation or size between the 3D model and the ilium of the patient was negligible during the surgery, although 2D images were not acquired from actual patient. Intraoperative contouring of the plate was not required. In conclusion, through presurgical plate contouring by the 3D bone template based on non-patient specific data, successful treatment of the ilial fracture was possible. Keywords: allogenic; cats; ilial fracture; 3D printing, 3D models, pilot study.